ANALISIS KEBUTUHAN DOMESTIK DI KECAMATAN MAULAFA TERHADAP KETERSEDIAAN AIR BERSIH - Fransiska C.N. Harmans; Agustinus H. Pattiraja; Oktovianus E. Semiun (Universitas Kristen Maranatha, 2022)
The rapid population growth of an area is usually followed by an increase in water demand. The current availability of water is not necessarily able to meet the increasing demand for clean water. Therefore, it is necessary to estimate how much clean water is needed for each household water tap in a community. Estimation is carried out by interpreting the current and projected number of residents and customers and comparing it with the production capacity of existing water sources. The results of the analysis based on the population growth rate and the number of customers show that the current demand for clean water is 135.80 liters/second, while the demand for clean water in the next 10 years is 165.26 liters/second, and 93.79 liters/second. The current ratio is 0%, while for the next 10 years the ratio will be 122% and 69%. Based on the population growth rate until 2030, the existing availability of clean water is not able to meet the future water demand of the community, while, based on customer growth, the availability of clean water is still able to meet the future water demand of customers.